171k views
4 votes
Evaluate the following.

*Be sure to write the full function notation statement.

f(3)=

Evaluate the following. *Be sure to write the full function notation statement. f-example-1
User Zin Min
by
4.3k points

2 Answers

4 votes

Answer:

t t vtvtvrshtzbzhtwvstwbwse DHS. sbsbsbsj

User VooD
by
4.6k points
6 votes

Answer: f(3) = -22

=======================================================

Step-by-step explanation:

Each time x goes up by 1, y decreases by 6. At the bottom row, we see that x = 2 and y = -16 pair up.

So when we get to the input 3, we'll drop that -16 by 6 to get -16-6 = -22 as the output of f(3).

User Denizeren
by
5.1k points